2023
DOI: 10.3390/antiox12030678
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thallium(I) on Growth, Nutrient Absorption, Photosynthetic Pigments, and Antioxidant Response of Dittrichia Plants

Abstract: Dittrichia plants were exposed to thallium (Tl) stress (10, 50, and 100 µM) for 7 days. The Tl toxicity altered the absorption and accumulation of other nutrients. In both the roots and the leaves, there was a decline in K, Mg, and Fe content, but an increase in Ca, Mn, and Zn. Chlorophylls decreased, as did the photosynthetic efficiency, while carotenoids increased. Oxidative stress in the roots was reflected in increased lipid peroxidation. There was more production of superoxide (O2.−), hydrogen peroxide (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 124 publications
0
5
0
Order By: Relevance
“…The different ROS-scavenging enzymes in plants, such as CAT, SOD and GSH reductase (GR), increase in parallel [10,26]. In a recent study [27] in which Dittrichia is challenged with Thallium(I), the authors showed that APX activity in leaves was just slightly increased by increasing concentrations of the HM, with a resulting H 2 O 2 concentration increment suggesting a weak increase in CAT activity. Also, GR activity did not change with the increasing concentration of HM.…”
Section: Discussionmentioning
confidence: 99%
“…The different ROS-scavenging enzymes in plants, such as CAT, SOD and GSH reductase (GR), increase in parallel [10,26]. In a recent study [27] in which Dittrichia is challenged with Thallium(I), the authors showed that APX activity in leaves was just slightly increased by increasing concentrations of the HM, with a resulting H 2 O 2 concentration increment suggesting a weak increase in CAT activity. Also, GR activity did not change with the increasing concentration of HM.…”
Section: Discussionmentioning
confidence: 99%
“…According to the in-depth search in the scientific literature, there is no previously published information to compare the effects of Cd, Tl and V on the photosynthetic parameters of three chili pepper varieties. However, several studies have documented the individual effects of these elements on plant physiology and metabolism, including photosynthesis [63][64][65].…”
Section: Instantaneous Carboxilation Efficiency (Pn/ci)mentioning
confidence: 99%
“…14 In Dittrichia plants exposed to 100 μM Tl, oxidative stress was observed as well as a decline of some nutrients (Fe, Mg, and K). 15 A study on Sinapsis alba (white mustard) showed that Tl tolerance decreased in higher Tl treatments, with evident effects on growth inhibition, oxidation of pigments, and a decline in photosystem core proteins. 16 Of all the nonessential trace elements, Tl has some of the highest bioaccumulation coefficients among plants, with high values reported in members of the Brassicaceae family.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A recent study on Arabidopsis thaliana reported that Tl interferes in K-dependent processes, inhibits photosynthetic activity, and enhances oxidative stress . In Dittrichia plants exposed to 100 μM Tl, oxidative stress was observed as well as a decline of some nutrients (Fe, Mg, and K) . A study on Sinapsis alba (white mustard) showed that Tl tolerance decreased in higher Tl treatments, with evident effects on growth inhibition, oxidation of pigments, and a decline in photosystem core proteins .…”
Section: Introductionmentioning
confidence: 99%